The effect of combined stimulation with maternal breast milk odor and non-nutritive sucking on the time of achieving independent oral feeding in premature infants - Khodagholi, zahra; Zarifian, Talieh; Soleimani, Farin; Khoshnood shariati, Maryam; Bakhshi, Enayatollah (Iranian Journal of Child Neurology, 2018)
Background and Objectives Given the positive effects of stimulation with maternal breast milk odor and non-nutritive sucking on premature infants’ feeding skills, the present study was conducted to examine the effect of combining two stimuli, including non-nutritive sucking and maternal breast milk odor, on the time of achieving independent oral feeding in premature infants. Materials and Methods The present clinical trial was conducted at Mahdieh and Shohada-e Tajrish Hospitals of Tehran in 2016. A total of 32 neonates with a fetal age of 28-32 weeks for whom gavage feeding was started entered the study and were divided into a group of non-nutritive sucking combined with olfactory stimuli and another group of non-nutritive sucking only. The stimulations were performed in both groups at the first five minutes of gavage, three times per day, over ten consecutive days. Weight gain, the time of achieving frequent oral feeding and chronological age at the time of discharge from the hospital were recorded as measures of the effectiveness of the interventions. The results of the interventions were analyzed and compared in SPSS-18. Findings and Conclusion Non-nutritive sucking combined with maternal breast milk odor leads to a lower post-menstrual age at the first oral feeding, independent oral feeding and discharge from the hospital in premature infants, but has no effects on their daily weight gain and weight at the time of discharge. These results show the effectiveness of combining maternal breast milk odor and non-nutritive sucking as two separate stimuli in achieving oral feeding and earlier discharge from the hospital.